Estabilidade de hematitas pedogênica e litogênica - Prudente, Carolina Borges (2017)
Much information is available in soil science on the stability of pedogenic hematite and goethite, but not on the stability of litogenic hematite present in red sandstones. This study investigates the stability of these two types of hematite in the face of dissolution by a reducing agent. The study included sandstone rocks from four formations and four samples of ferric, basalt-derived Latosol from different regions in Brazil. The sandstone samples were ground and had their silt + clay fractions separated for mineralogical analysis. Initially, iron oxides were concentrated for slide preparation by using X-ray diffraction for mineralogical analyses. Then, four successive iron extractions were carried out through dissolution by using reducing agent sodium dithionite-citrate- bicarbonate (DCB) on thin air-dried earth. In addition, total iron (Fet) was measured by using sulfuric attack and X-ray fluorescence spectrometry. The results indicate that the best definition of X-ray peaks for lithogenic hematite is a characteristic that reveals better crystallinity and consequently greater resistance to reduction (solubilization by DCB80) than those observed in pedogenic hematite. In the X-ray diffractograms, very little variation was observed in the position of hematite reflections in both environments, indicating structural proximity. The results obtained by X-ray fluorescence spectrometry proved to be an important auxiliary technique in the mineralogical study.